2012
DOI: 10.3390/molecules17078578
|View full text |Cite
|
Sign up to set email alerts
|

A Facile and Efficient Procedure for the Synthesis of New Benzimidazole-2-thione Derivatives

Abstract: A series of benzimidazole-2-thione derivatives was synthesized using a reaction between the macrocyclic aminal 16H,13H-5:12,7:14-dimethanedibenzo[d,i]-[1,3,6,8] tetraazecine (DMDBTA, 5) and various nucleophiles in the presence of carbon disulfide. A full chemical characterization using IR, 1H-, 13C-NMR and GC-MS analyses of the new compounds is provided. These compounds were separated from the reaction mixture by column chromatography (CC) in highly pure form in 15%–51.4% yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…It then undergoes through a cyclization process in which the intramolecular nucleophilic attack on the imine carbon form 5-membered imidazoline ring. The latter is prone to fast oxidation into aromatic imidazole motif by action of air oxygen, which is well-documented in the literature [ [37] , [38] , [39] , [40] ].
Scheme 2 Proposed mechanism for the formation of imidazole phenazine derivatives 3a-3m via condensation reaction [ 41 ].
…”
Section: Resultsmentioning
confidence: 97%
“…It then undergoes through a cyclization process in which the intramolecular nucleophilic attack on the imine carbon form 5-membered imidazoline ring. The latter is prone to fast oxidation into aromatic imidazole motif by action of air oxygen, which is well-documented in the literature [ [37] , [38] , [39] , [40] ].
Scheme 2 Proposed mechanism for the formation of imidazole phenazine derivatives 3a-3m via condensation reaction [ 41 ].
…”
Section: Resultsmentioning
confidence: 97%
“…5) is an organosulfur compound with the formula of S=C(NH2)2. This compound and its derivatives, in particular, have showed various pharmacological activities such as anti-fungal (58,59) , antiviral (58,60) , anticancer (61) , antituberculosis (62) , antimicrobial (63) and anti-inflammatory (64)(65)(66) . Thiourea has gained significant values since being studied for their application in commercial and industrial applications; plastics, textiles dyes, elastomer, herbicides, pesticides, rodenticides and catalytic (65,67,68) .…”
Section: Nosh-aspirin As Anti-inflammatory and Anticancer Agentmentioning
confidence: 99%
“…However, the most significant and effective application of thiourea is in the realm of biology, as illustrated in Figure 3. Research has demonstrated that it possesses numerous beneficial properties, including antibacterial, antioxidant, anticancer, anti-inflammatory, anti-Alzheimer, antitubercular and antimalarial effects [4][5][6][7][8][9]. Several previous reviews have focused on the pharmacological activities of thiourea derivatives [10][11][12].…”
Section: Introductionmentioning
confidence: 99%